The effects of ability to change answers on computer-based test performance of associate degree nursing students. - Steadman MF (Effects of Ability to Change Answers on Computer-based Test Performance of Associate Degree Nursing Students, 1997)
High stakes exams such as the National Council Licensure Examination (NCLEX), given in the format of computer-adapted testing, allow examinees no control over the order in which test items are answered and reviewed, and no control over the ability to change answers. Traditionally, students have been trained in test-taking skills using paper-and-pencil tests which allow them control, and studies have consistently shown that changing answers increases test scores. The purpose of this study was to explore the impact of ability to review questions and change answers in a computer-based testing (CBT) situation.The subjects were 99 nursing students in their second year of a two-year associate degree nursing program. This was a mixed-method study in that both quantitative and qualitative methods were used. Quantitative questions were answered by analyzing the results of an experiment in which students taking a regular course examination were randomly assigned to either an experimental group which could not review questions or change answers, or a control group which could do so. The examinees differed in level of anxiety, as measured by the State Anxiety Scale of Spielberger's State-Trait Anxiety Inventory, as well as on desire to review items and change answers, as determined by self-report on the Exploratory Questionnaire developed for this study. Qualitative questions were answered by analyzing data generated by an open-ended question on the questionnaire and by individual, in-depth interviews with 10 students randomly selected from the subjects.Results indicated no difference in the performance of the two groups. When given a choice, examinees revealed, both in their test-taking behaviors as recorded by the computer and through discussion, their preference to review questions and change answers. By maintaining performance levels, they showed their ability to adapt to the demands of the testing situation in which they could not review questions or change answers.An intended outcome of this study was to determine helpful test-taking techniques for situations when it is not possible to review questions and change answers. There were three major themes for recommendations to examinees: (a) take your time in answering questions, (b) read the questions thoroughly, and (c) be prepared for the test.